Visualization of Air Quality Movement for Health Care Sector - Zhou SHUO; Doris Hooi-Ten WONG; Nurazean MAAROP (Communications of International Proceedings, 2022)
In 2020, A new form of coronavirus pneumonia has ravaged the world. The epidemic has not only hit the economy hard, but has also had a significant impact on air quality. COVID-19 virus' primary target is the human respiratory system. Air quality is most relevant to breathing. Although many studies have been conducted in the literature on the impact of the environment on the epidemic, there are no studies specifically for Korea. Seoul being the capital of the country, it is very important to investigate the air quality in Korea as factors for the increase of the epidemic, which is of great significance and value for decision making. The objectives of this study is to identify the factors of the air quality lead to spread of COVID -19. Next, to design visualization of air quality and covid-19 data by using Tableau.  This study identifies the evolution pattern of air quality in Seoul, Korea, clarifies the effect of the epidemic on air quality reduction in Seoul, and reveals the mechanism of the effect of the epidemic on air quality in Seoul, Korea.The main research contribution is to evaluate the accuracy of visual analysis of air quality data through different. Help the health care sector to raise awareness of preventive public health, take environmental management measures, implement construction and improve related regulations, and continue to strengthen ecological and environmental protection.
Keywords: COVID -19; Air quality; Tableau; Health care sector